Nucleobase Modified Adefovir (PMEA) Analogues as Potent and Selective Inhibitors of Adenylate Cyclases from Bordetella pertussis and Bacillus anthracis - Česnek, Michal; Skácel, Jan; Jansa, Petr; Dračínský, Martin; Šmídková, Markéta; Mertlíková-Kaiserová, Helena; Soto-Velasquez, Monica P; Watts, Val J; Janeba, Zlatko (ChemMedChem, 2018)
A series of 13 acyclic nucleoside phosphonates (ANPs) as bisamidate prodrugs was prepared. Five compounds were found to be non-cytotoxic and selective inhibitors of Bordetella pertussis adenylate cyclase toxin (ACT) in J774A.1 macrophage cell-based assays. The 8-aza-7-deazapurine derivative of adefovir (PMEA) was found to be the most potent ACT inhibitor in the series (IC50 =16 nm) with substantial selectivity over mammalian adenylate cyclases (mACs). AC inhibitory properties of the most potent analogues were confirmed by direct evaluation of the corresponding phosphonodiphosphates in cell-free assays and were found to be potent inhibitors of both ACT and edema factor (EF) from Bacillus anthracis (IC50 values ranging from 0.5 to 21 nm). Moreover, 7-halo-7-deazapurine analogues of PMEA were discovered to be potent and selective mammalian AC1 inhibitors (no inhibition of AC2 and AC5) with IC50 values ranging from 4.1 to 5.6 μm in HEK293 cell-based assays.
Keywords: Adenylyl Cyclases; Bacillus anthracis; vztahy mezi strukturou a aktivitou; Molecular Structure; Enzyme Inhibitors; Bordetella pertussis; Structure-Activity Relationship; vztah mezi dávkou a účinkem léčiva; molekulární struktura; organofosfonáty; Dose-Response Relationship, Drug; adenin; Organophosphonates; adenylátcyklasy; Adenine; inhibitory enzymů